Assessing students' academic quality performance / Norlaila Abdullah and Zuhariah Husin - Abdullah, Norlaila; Husin, Zuhariah (2008)
Achieving quality objectives is paramount to everyone in an organization. This is a preliminary paper that attempts to analyze and measure the academic performance of students in three selected diploma programs of UiTM Pahang. Three elements encompassing students' graduating on time, students completing beyond the allotted time (extend students) and those graduating with CGPA greater than 3.00 are the fundamental focus of this study. Analysis reveals similar academic quality patterns and trends for the two of the three programs studied while intermittent CGPA performance for the remainder. Based on Pareto principle, the study indicates that the cause of lower quality academic performance is dominated by 30% of the students' population and solving this would contribute to 70% of lecturers' time for publications and writings. Finally, a suggested Pro-Forma cost of Quality report has been initially devised as a tool for monitoring programs' quality performances.